2008
DOI: 10.1161/circresaha.107.167817
|View full text |Cite
|
Sign up to set email alerts
|

Spatiotemporal Dynamics of β-Adrenergic cAMP Signals and L-Type Ca 2+ Channel Regulation in Adult Rat Ventricular Myocytes

Abstract: Abstract-Steady-state activation of cardiac ␤-adrenergic receptors leads to an intracellular compartmentation of cAMP resulting from localized cyclic nucleotide phosphodiesterase (PDE) activity. To evaluate the time course of the cAMP changes in the different compartments, brief (15 seconds) pulses of isoprenaline (100 nmol/L) were applied to adult rat ventricular myocytes (ARVMs) while monitoring cAMP changes beneath the membrane using engineered cyclic nucleotide-gated channels and within the cytosol with th… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

19
153
2
5

Year Published

2011
2011
2016
2016

Publication Types

Select...
7
1

Relationship

2
6

Authors

Journals

citations
Cited by 144 publications
(179 citation statements)
references
References 35 publications
19
153
2
5
Order By: Relevance
“…Immunohistochemistry shows that PDE2 and PDE4 are localized at the sarcomeric Z line suggestive of anchoring to subcellular structures, whereas PDE3 is associated with internal membranes like the sarcoplasmic reticulum (252,253). Live-cell imaging reveals a variable increase in cAMP due to PDE3 and PDE4 inhibition in ventricular myocytes, confirming the existence of distinct subcellular compartments (204). Assuming PDE localization correlates to function, one could hypothesize that PDE3 regulates cAMP-mediated cardiac contractility while PDE4 regulates ␤-AR-sensitive cAMP microdomains.…”
Section: A Physiological Implication For Localization and Function Omentioning
confidence: 87%
See 2 more Smart Citations
“…Immunohistochemistry shows that PDE2 and PDE4 are localized at the sarcomeric Z line suggestive of anchoring to subcellular structures, whereas PDE3 is associated with internal membranes like the sarcoplasmic reticulum (252,253). Live-cell imaging reveals a variable increase in cAMP due to PDE3 and PDE4 inhibition in ventricular myocytes, confirming the existence of distinct subcellular compartments (204). Assuming PDE localization correlates to function, one could hypothesize that PDE3 regulates cAMP-mediated cardiac contractility while PDE4 regulates ␤-AR-sensitive cAMP microdomains.…”
Section: A Physiological Implication For Localization and Function Omentioning
confidence: 87%
“…The catalytic activities of PDEs provide for breakdown of cNs over a spectrum of concentrations in all cells, and their varied regulatory mechanisms provide for integration and crosstalk with myriad signaling pathways. It has recently been established that particular PDEs are targeted to discrete compartments within cells where they control cN level and sculpt microenvironments for a variety of cN signalosomes that can contain cN-dependent protein kinases, Epacs (exchange proteins activated by cAMP), phosphoprotein phosphatases, and/or cN-gated cation channels (14,30,49,58,70,104,153,158,167,170,204,299,387,391,422,423). Localization of some PDEs to specific areas of a cell is static, whereas that for others involves reversible recruitment (153).…”
Section: Overview Of the 11 Families And Isoenzymes Within Familiementioning
confidence: 99%
See 1 more Smart Citation
“…We previously showed that the β-AR stimulation of I Ca,L is under the control of PDE4 in adult rat ventricular myocytes (18). To determine whether the same was true in mice, I Ca,L was recorded in adult mouse ventricular myocytes (AMVMs) using the whole-cell patch-clamp technique, and the response of this current to a short application of the nonselective β-AR agonist isoprenaline (Iso) was studied.…”
Section: β-Ar Stimulation Of I Cal and Effect Of Pde4 Inhibition In mentioning
confidence: 99%
“…Dans la plupart des espèces, l'inhibition des PDE4 n'exerce peu ou pas d'effet inotrope positif direct, mais devient importante lorsque les taux d'AMPc sont augmentés [16,27]. Par exemple, chez le rat, l'inhibition des PDE4 n'a aucun effet sur l'AMPc, I Ca,L et le CEC en conditions basales, mais devient prédominante pour contrôler ces paramètres lors d'une stimulation -AR ou lors de l'inhibition concomitante de la PDE3 [21,28] (D. Mika, J. Leroy, R. Fischmeister, G. Vandecasteele ; résultats non publiés). Chez la souris, l'inhibition des PDE4 n'a pas d'effet sur I Ca,L en conditions basales, mais potentialise fortement les effets d'une stimulation -AR sur I Ca,L et sur la contraction [29].…”
Section: Régulation Du Cec Par Les Pde4unclassified